SURGICAL OUTCOME OF SUPRATENTORIAL LOW GRADE GLIOMAS: STUDY OF 85 CASES - Ul Haq, Naeem; Ali, Mumtaz; Usman, Muhammad; Zar Khan, Bakht; Azam, Farooq (Journal of Postgraduate Medical Institute, 2016)
Objective: To determine the surgical outcome of supratentorial low grade gliomas. Methodology: This prospective study was conducted in Department of Neurosurgery Lady Reading Hospital Peshawar from December 2009 to November 2013. All patients who were operated for supratentorial low grade gliomas were included in the study while operated patients of infra tentorial gliomas, high grade gliomas, and other tumors of the brain were excluded from the study. Patient's age, gender, pre-operative sign and symptoms, location of glioma, post operative outcome and type of glioma based on histopathology were recorded on predesigned proforma. Post op follow up was done up to 1 year. All the data was analyzed by SPSS 16 and results were presented in the form of tables/graphs/charts. Results: We included 85 patients in this study, males 50(58%) were and females were 35(41%). Age ranged from 18 to 80 years with mean 49 ±5 years. Pre-operative Kernofsky performance score (KPS) was 90 in 38(45%) and 80 in 17(20%). On neuroimaging frontal lobe was most commonly involved i.e. in 44(50%). Based on histopathology astrocytoma grade II was the commonest and reprted in 34(40%) cases. Gross total resection was done in 29(35%) patients while subtotal resection in 56(65%). Post-operatively headache and vomiting improved in 44 (50%) patients and seizures in 47(56%) patients. KPS improved in 24 (28%) patients while deteriorated in 3(3.5%) patients. Conclusion: Concious level, Kernofsky performance score, control of seizures and headache are important parameters for surgical outcome in patients with low grade gliomas and improved in significant number of our patients.